Nose to Brain Delivery: New Trends in Amphiphile-Based “Soft” Nanocarriers - Marianecci, Carlotta; Rinaldi, Federica; N. Hanieh, Patrizia; Paolino, Donatella; Di Marzio, Luisa; Carafa, Maria (Current Pharmaceutical Design, 2015)
The aim of the present paper is to highlight the potential of nasal mucosa as an administration route for targeting the central nervous system, in particular, the brain. Among the formulation strategies for enhance nose to brain drug delivery, the use of colloidal carriers has became a revolutionary approach. These systems should be able to entrap drugs in the desired amount, to penetrate through anatomical barriers, to efficiently release the loaded drugs in the site of action and moreover to show a good physicochemical, biological stability and good biocompatibility. The use of vesicular systems (liposomes and niosomes) together with the use of micelles, in nose to brain delivery are here presented. Vesicle structure is characterized by the presence of a hydrophobic bilayer and an aqueous core that is absent in micelles. Amphiphilic molecules are responsible for soft nanocarriers formation, in particular: liposomes are formed by phospholipids, while niosomes by non-ionic surfactant and micelles by amphiphilic polymers.
Keywords: central nervous system